Teacher Creativity Enhances Children's Cognitive Development through Traditional Games in Muslim Educational Institutions - Zulfa, Mona Yulia; Elia, Elia; Ahmad, Nurasiah; Nafsiyati, Hilma; Syahminal, Syahminal; Husni, Afdhalul; Uldiman, Uldiman (Sekolah Tinggi Ilmu Tarbiyah (STIT) Ahlussunnah Bukittinggi, 2024)
Early childhood cognitive development is a critical phase that requires appropriate stimulation to support logical thinking abilities and the use of basic concepts. Traditional games such as congklak have the potential to be an effective learning medium. This research aims to evaluate the influence of the conventional media game Congklak Geometric in improving the cognitive development of early childhood. This research uses the Research and Development method with the Analysis, Design, Development or Production, Implementation or Delivery, and Evaluation (ADDIE) model, which is then tested in a learning process involving fifteen students as research subjects. All data was analysed using correlation analysis techniques with IBM SPSS 25 Software. The results of the analysis regarding the use of geometrically shaped congklak media products show the criteria i) material aspect, 87.50%, ii) cognitive aspect, 82.50%, iii) media aspect, 82.16% with a total average of 84.16%. Furthermore, the results of statistical analysis show that congklak media is proven to be able to stimulate the cognitive development of young children with a focus on geometric shapes in the learning process with a total average of 84.16%. The findings of this research indicate that the geometric congklak game can be integrated into the early childhood education curriculum as an effective strategy to support cognitive development.